Estimation of Mycophenolic Acid Exposure in Heart Transplant Recipients by Population Pharmacokinetic and Limited Sampling Strategies - Wang, Xipei; Wu, Yijin; Huang, Jinsong; Shan, Songgui; Mai, Mingjie; Zhu, Jiade; Yang, Min; Shang, Dewei; Wu, Zheng; Lan, Jinhua; Zhong, Shilong; Wu, Min (Frontiers in Pharmacology, 2021)
Purpose The aim of this study is (i) to establish a strategy to estimate the area under the curve of the dosing interval (AUC0-12h) of mycophenolic acid (MPA) in the heart transplant recipients, and (ii) to find the covariates that significantly affect the pharmacokinetics of MPA exposure. Methods This single-center, prospective, open-label, observational study was conducted in 91 adult heart transplant recipients orally taking mycophenolate mofetil dispersible tablets. Samples collected intensively and sparsely were analyzed by enzyme multiplied immunoassay technique and all the data were used in PPK modeling. Potential covariates were tested stepwise. The goodness-of-fit plots, the normalized prediction distribution error and prediction corrected visual predictive check were used for the model evaluation. Optimal sampling times by ED-optimal strategy and multi-linear regression (MLR) were analyzed based on the simulated data by the final PPK model. Moreover, using the intensive data from 14 patients, the accuracy of AUC0-12h estimation was evaluated by Passing-Bablok regression analysis and Bland-Alman plots for both PPK model and MLR equation. Results A two-compartment model with first-order absorption and elimination with a lag time was chosen as the structure model. Co-medication of proton pump inhibitors (PPIs), estimated glomerular filtration rate (eGFR), and albumin (ALB) were found to significantly affect bioavailability (F), clearance of central compartment (CL/F) and the distribution volume of the central compartment (V2/F), respectively. Co-medication of PPIs decreased F by 27.6%. When eGFR decreased by 30 mL/min/1.73 m2, CL/F decreased by 23.7%. However, the impact of ALB on V2/F was limited to MPA exposure. The final model showed an adequate fitness of the data. The optimal sampling design was pre-dose and 1 and 4 h post-dose for pharmacokinetic estimation. The best-fit linear equation was finally established: AUC0-12h = 3.539 × C0 + 0.288 × C0.5 + 1.349 × C1 + 6.773 × C4.5. Conclusions A PPK model was established with three covariates in heart transplant patients. Co-medication of PPIs and eGFR had a remarkable impact on AUC0-12h of MPA. A linear equation was also concluded with four-time points as an alternative way to estimate AUC0-12h for MPA.